Outcomes of patients with high bleeding risks characteristics presenting with acute coronary syndrome undergoing percutaneous coronary intervention. (14th October 2021) - Fu, A; Barry, Q; Boudreau, R; Clifford, C; Chow, A; Simard, T; Chong, A Y; Dick, A; Froeschl, M; Glover, C; Hibbert, B; Labinaz, M; et al.
Abstract: Background: Patients with high bleeding risk characteristics (HBR) presenting with acute coronary syndrome (ACS) pose a clinical challenge to balance risk for recurrent ischemic events versus incurring bleeding with dual antiplatelet therapy. Purpose: We seek to determine the incidence and predictors of short and long term ischemic and bleeding outcomes in patients with HBR factors presenting with ACS after percutaneous coronary intervention (PCI). Method: Consecutive patients over a 1-year period, who underwent PCI for ACS were categorized as having HBR based on: age ≥75, anemia (hemoglobin<110g/L), thrombocytopenia (platelet<100x10 9 /L), renal failure (eGFR<30umol/L) or concurrent use of oral anticoagulation. Primary outcome was major adverse cardiovascular event (MACE) defined as composite of cardiovascular death, myocardial infarction, and stroke at 1 year. Key secondary outcomes include significant bleeding defined as Bleeding Academic Research Consortium (BARC) type 3 or 5, and net adverse cardiovascular event (NACE), as a composite of MACE and significant bleeding. Results: Of 1351 patients presented with ACS, 389 (28.8%) had at least one HBR criteria. At 1 year, patients with HBR, compared to those without, had increased MACE (11.1% vs 4.2%, p<0.001) and cardiovascular death (5.7% vs 1.7%, p<0.001). Patients with HBR had increased significant bleeding (3.6% vs 2.3%, p=0.011) and NACE (14.4% vs 5.4%, p<0.001). Multivariate analysis showed the presence of HBR and prior history of myocardial infarction were predictors for 1-year MACE (OR 2.67, CI [1.62–4.42], p<0.001 and OR 2.18, CI [1.29–3.70], p=0.004, respectively), whereas the use of second-generation antiplatelet agent was not. Increased MACE and NACE were observed in HBR patients beyond 1 month of DAPT. Conclusion: Among patients with ACS undergoing PCI, those with HBR had higher risk for both ischemic and bleeding complications. Novel strategies need to be considered for this high-risk group. Current guidelines, recommending 1 year of DAPT for patients with ACS, should be re-evaluated among patients with HBR. FUNDunding Acknowledgement: Type of funding sources: None.